The Sustainable Development Goal 2 Dalam Sudut Pandang At-Tikrār fĭ al-Qur’ān - Supriyanto, Sodik; Misbakhudin (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2024)
SDGs that have been introduced for many years, have several goals for humans. The repetition of the words eat and drink in the Qur’an may correlated with Sustainable Development Goal 2 which is Zero Hunger to eliminate hunger, to achieve food and nutrition retention, and improving sustainable agriculture. The Qur'an that has existed from revelation will always be relevant in every era with its each context. The Qur'an will always be a guidence for every challenge of the changing times. The repetition of the word (tikrār) kulū wasyrabū in the Qur'an has a lot of wisdom and lot of teachings to be learned. The Interpretation of Tikrār of word kulū wasyrabū raises several concepts and values that could help the understanding of the context of sustainable food needs. This is a qualitative and library research with its primary and secondary data and delivered in a descriptive narration which explains the goals of Sustainable Development Goal 2: No Hunger, and explains the tikrār verses in the Qur'an, explains concepts, values and its implementation in everyday life to provide a great opportunity in realizing the zero hunger goal.